Anti-aging nano calcium carbonate surface treatment method for photovoltaic sealant and photovoltaic sealant

By applying surface treatment of nano calcium carbonate with mono-fatty acid glyceride, 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine and sodium phosphite, the problem of insufficient anti-aging performance of nano calcium carbonate in photovoltaic sealants is solved, especially in terms of ultraviolet resistance, the performance of photovoltaic glue is significantly improved and the yellowing phenomenon is reduced.

CN119799034AActive Publication Date: 2025-04-11XIANGYANG XINGFA CHEM CO LTD

Patent Information

Application Number
CN202411762869.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-04-11
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

The nano calcium carbonate in existing photovoltaic sealants lacks anti-aging properties, especially in terms of resistance to ultraviolet, which leads to yellowing problems in photovoltaic modules during long-term outdoor use.

Method used

The nano calcium carbonate is modified by using surface treatment agents such as mono-fatty acid glycerides, 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine and sodium phosphite to improve its anti-humidity and ultraviolet properties in photovoltaic glue.

Benefits of technology

The modified nano calcium carbonate shows better dispersion, specific surface area and UV resistance in photovoltaic glue, which significantly improves the durability and stability of photovoltaic glue and reduces yellowing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119799034A_ABST
    Figure CN119799034A_ABST
Patent Text Reader

Abstract

The invention relates to a surface treatment method of anti-aging nano calcium carbonate for a photovoltaic sealant. Surface treatment is carried out on nano calcium carbonate by using glyceryl monostearate, 2, 4, 6-tri (4-carboxyphenyl)-1, 3, 5-triazine and sodium phosphite, and the nano carbonate treated by the method has relatively high activity and good dispersity, has good resistance to damp-heat aging and ultraviolet aging when being applied to photovoltaic glue, and has good application prospects. Therefore, the problems of aging and yellowing of the existing photovoltaic adhesive are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nano-scale calcium carbonate preparation and relates to a surface treatment method for anti-aging nano-calcium carbonate of photovoltaic sealant. Background Art

[0002] As a neutral one-component silicone sealant that can be cured at room temperature, silicone photovoltaic adhesive is widely used in the bonding of external frames and junction boxes of solar photovoltaic modules due to its fast deep curing, excellent bonding performance, non-corrosiveness to metals and environmental protection. Photovoltaic modules need to operate stably in harsh outdoor environments for a long time, which places strict requirements on the weather resistance of the sealants used. The aging and yellowing problem is one of the main challenges facing the application of silicone in the photovoltaic industry.

[0003] Chinese invention patent CN116282115A discloses a method for preparing nano calcium carbonate for photovoltaic sealant, which is prepared by calcining, digesting, refining and screening limestone, adding a dispersant and grinding and dispersing to obtain raw pulp, adding crystal control and kiln gas to obtain nano calcium carbonate slurry, adding a composite surface treatment agent to the nano calcium carbonate slurry to obtain a modified calcium carbonate slurry, and filtering, drying, crushing, grading and packaging the modified calcium carbonate slurry to obtain a nano calcium carbonate product for photovoltaic sealant. Its beneficial technical effects are: when nano calcium carbonate is processed and filled with silicone sealant, it is easy to process, has low viscosity and good dispersibility, the raw materials used in this method are cheap and easy to obtain, low cost, simple and feasible process, suitable for industrial production, and has good economic and social benefits, but lacks anti-aging related properties. Chinese invention patent CN10886473A discloses a surface treatment method for nano calcium carbonate used in silicone sealant for photovoltaic modules. The invention uses beef tallow and ammonium polyphosphate for the first modification and uses carboxyl-terminated polyester and phosphite for the second modification. The modified nano calcium carbonate also has moisture and heat resistance, high temperature resistance and oxidation resistance. When used for filling photovoltaic glue, it can improve the mechanical properties of photovoltaic glue and enhance the moisture and heat resistance and high temperature resistance of photovoltaic glue, but it still has shortcomings in terms of UV resistance.

[0004] Chinese invention patent CN105778568A discloses a surface treatment method for nano calcium carbonate used in photovoltaic adhesives, which uses a compound surface treatment agent to perform surface treatment to obtain modified nano calcium carbonate. The nano calcium carbonate of this invention is used to fill photovoltaic adhesives, which not only ensures excellent processing and mechanical properties of the colloid, but also has good low viscosity, good thixotropy, high tensile strength and resistance to moisture and heat aging, but also has shortcomings in terms of UV resistance.

[0005] In summary, it is necessary to seek a nano calcium carbonate that can not only give photovoltaic adhesive good resistance to moisture and heat aging, but also provide better anti-ultraviolet effect to solve the yellowing problem. Summary of the invention

[0006] The purpose of the present invention is to provide a method for preparing anti-aging nano calcium carbonate for photovoltaic sealant. The present invention has anti-ultraviolet effect on the basis of moisture resistance and heat resistance.

[0007] The present invention uses monostearate, 2, 4, 6-tris(4-carboxyphenyl)-1, 3, 5-triazine and sodium phosphite to perform surface treatment on nano calcium carbonate. The nano calcium carbonate treated by the method has high activity and good dispersibility. In photovoltaic adhesive applications, the nano calcium carbonate has good resistance to wet heat aging and ultraviolet aging.

[0008] The specific implementation steps of the present invention are as follows: A surface treatment method for anti-aging nano calcium carbonate of photovoltaic adhesive sealant comprises the following steps: (1) Add nano calcium carbonate slurry into a reactor and heat it to 60-90°C; (2) adding the prepared surface treatment agent to the slurry of step (1) for surface treatment, and stirring to obtain modified nano calcium carbonate slurry; (3) Dehydrating, drying and crushing the obtained modified nano-calcium carbonate slurry to obtain a nano-calcium carbonate product.

[0009] The specific surface area of ​​nano calcium carbonate is 15-35m2 / g, and the concentration of nano calcium carbonate slurry is 14%-17%.

[0010] The surface treatment agent is a mixture of monostearate, 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine and sodium phosphite.

[0011] The mass ratio of monostearate to 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine and sodium phosphite is 15-35:1:2-5.

[0012] The added amount of the surface treatment agent is 0.1% to 0.5% of the mass of nano calcium carbonate.

[0013] After adding the surface treatment agent, stirring is performed at 1200-1800 r / min to obtain modified nano calcium carbonate slurry.

[0014] The drying temperature in step (3) is 105°C to 125°C.

[0015] The key technical feature of the present invention is to prepare a surface treatment agent using monostearate, 2, 4, 6-tris(4-carboxyphenyl)-1,3, 5-triazine and sodium phosphite in a corresponding proportion, and then perform surface treatment on a high-concentration nano calcium carbonate slurry using high-speed stirring. Compared with the existing nano calcium carbonate surface modified with stearic acid, the product of the present invention has better dispersibility, higher specific surface area and lower oil absorption value; in photovoltaic adhesive applications, it can provide good UV resistance on the basis of existing performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The electron microscope images of nano-calcium carbonate obtained in Example 2 and Comparative Example 1 are shown in Figure 2, a) is Comparative Example 1, and b) is Example 2.

[0017] Figure 2 This is the UV-visible absorption spectrum of 2, 4, 6-tris(4-carboxyphenyl)-1, 3, 5-triazine; it can be seen that the compound has good anti-ultraviolet properties.

[0018] Figure 3 It is a diagram of the moisture and heat resistance and high temperature test of Example 2 and Comparative Example 1, with Example 2 on the left and Comparative Example 1 on the right.

[0019] Figure 4 These are UV aging test diagrams of Example 2 and Comparative Example 1, with Example 2 on the left and Comparative Example 1 on the right. DETAILED DESCRIPTION

[0020] The present invention will be further described below through specific implementation: Example 1 A surface treatment method for anti-aging nano calcium carbonate of photovoltaic adhesive sealant comprises the following steps: (1) adding a nano-calcium carbonate slurry with a concentration of 15.1% and a BET of 27.5 m2 / g into a reaction kettle, stirring, and heating to 80°C; (2) adding the surface treatment agent of the present invention to the slurry of step (1) for surface treatment (monostearyl fatty acid glyceride: 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine: sodium phosphite = 15:1:2), wherein the amount of the composite surface treatment agent added is 0.2% of the mass of the nano-calcium carbonate in the slurry, and stirring at 1500r / min for 35min to obtain modified nano-calcium carbonate; (3) dehydrating the modified nano calcium carbonate by filter pressing, and drying at a drying temperature of 110° C. to obtain a dry material; (4) The dried material is then crushed, graded and packaged according to a conventional method to obtain a nano calcium carbonate product. Example 2 A surface treatment method for anti-aging nano calcium carbonate of photovoltaic adhesive sealant comprises the following steps: (1) adding a nano-calcium carbonate slurry having a concentration of 15.1% and a BET of 27.5 m2 / g into a reaction kettle, stirring, and heating to 80°C; (2) adding the surface treatment agent of the present invention to the slurry of step (1) for surface treatment (monostearyl fatty acid glyceride: 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine: sodium phosphite = 20:1:3), wherein the amount of the composite surface treatment agent added is 0.3% of the mass of the nano-calcium carbonate in the slurry, and stirring at 1500r / min for 35min to obtain modified nano-calcium carbonate; (3) dehydrating the modified nano calcium carbonate by filter pressing, and drying at a drying temperature of 110° C. to obtain a dry material; (4) The dried material is then crushed, graded and packaged according to a conventional method to obtain a nano calcium carbonate product.

[0021] from Figure 1 It can be seen that the electron microscopy of the present invention is more uniform, and its dispersibility is stronger than that of the existing stearic acid surface treatment agent modification.

[0022] from Figure 3 It can be seen that under the same conditions, the present invention is not significantly different from Comparative Example 1, and there is no obvious difference in resistance to wet heat aging.

[0023] from Figure 4 It can be seen that the redness degree in Comparative Example 1 is significantly higher than that in the present invention, which shows that the present invention has obvious advantages in anti-ultraviolet performance.

[0024] Example 3 A surface treatment method for anti-aging nano calcium carbonate of photovoltaic adhesive sealant comprises the following steps: (1) adding a nano-calcium carbonate slurry having a concentration of 15.6% and a BET of 28.2 m2 / g into a reaction kettle, stirring, and heating to 80°C; (2) adding the surface treatment agent of the present invention to the slurry of step (1) for surface treatment (monostearyl fatty acid glyceride: 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine: sodium phosphite = 20:1:4), wherein the amount of the composite surface treatment agent added is 0.3% of the mass of the nano-calcium carbonate in the slurry, and stirring at 1500r / min for 35min to obtain modified nano-calcium carbonate; (3) dehydrating the modified nano calcium carbonate by filter pressing, and drying at a drying temperature of 110° C. to obtain a dry material; (4) The dried material is then crushed, graded and packaged according to a conventional method to obtain a nano calcium carbonate product.

[0025] Example 4 A surface treatment method for anti-aging nano calcium carbonate of photovoltaic adhesive sealant comprises the following steps: (1) adding a nano-calcium carbonate slurry having a concentration of 15.6% and a BET of 28.2 m2 / g into a reaction kettle, stirring, and heating to 80°C; (2) adding the surface treatment agent of the present invention to the slurry of step (1) for surface treatment (monostearyl fatty acid glyceride: 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine: sodium phosphite = 35:1:5), wherein the amount of the composite surface treatment agent added is 0.4% of the mass of the nano-calcium carbonate in the slurry, and stirring at 1500r / min for 35min to obtain modified nano-calcium carbonate; (3) dehydrating the modified nano calcium carbonate by filter pressing, and drying at a drying temperature of 110° C. to obtain a dry material; (4) The dried material is then crushed, graded and packaged according to a conventional method to obtain a nano calcium carbonate product.

[0026] Example 5 A surface treatment method for anti-aging nano calcium carbonate of photovoltaic adhesive sealant comprises the following steps: (1) adding a nano-calcium carbonate slurry having a concentration of 15.6% and a BET of 28.2 m2 / g into a reaction kettle, stirring, and heating to 80°C; (2) adding the surface treatment agent of the present invention to the slurry of step (1) for surface treatment (monostearyl fatty acid glyceride: 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine: sodium phosphite = 28:1:3.5), wherein the amount of the composite surface treatment agent added is 0.5% of the mass of the nano-calcium carbonate in the slurry, and stirring at 1500r / min for 35min to obtain modified nano-calcium carbonate; (3) dehydrating the modified nano calcium carbonate by filter pressing, and drying at a drying temperature of 110° C. to obtain a dry material; (4) The dried material is then crushed, graded and packaged according to a conventional method to obtain a nano calcium carbonate product.

[0027] Comparative Example 1 A surface treatment method of existing nano calcium carbonate comprises the following steps: (1) adding a nano-calcium carbonate slurry with a concentration of 15.1% and a BET of 27.5 m2 / g into a reaction kettle, stirring, and heating to 80°C; (2) adding a stearic acid surface treatment agent to the slurry of step (1) for surface treatment, wherein the amount of the stearic acid surface treatment agent added is 0.3% of the mass of the nano-calcium carbonate in the slurry, and stirring at 1500 r / min for 35 min to obtain modified nano-calcium carbonate; (3) dehydrating the modified nano calcium carbonate by filter pressing, and drying at a drying temperature of 110° C. to obtain a dry material; (4) The dried material is then crushed, graded and packaged according to a conventional method to obtain a nano calcium carbonate product.

[0028] Comparative Example 2 A surface treatment method of existing nano calcium carbonate comprises the following steps: (1) adding a nano-calcium carbonate slurry with a concentration of 15.6% and a BET of 28.2 m2 / g into a reaction kettle, stirring, and heating to 80°C; (2) adding a stearic acid surface treatment agent to the slurry of step (1) for surface treatment, wherein the amount of the stearic acid surface treatment agent added is 0.5% of the mass of the nano-calcium carbonate in the slurry, and stirring at 1500 r / min for 35 min to obtain modified nano-calcium carbonate; (3) dehydrating the modified nano calcium carbonate by filter pressing, and drying at a drying temperature of 110° C. to obtain a dry material; (4) The dried material is then crushed, graded and packaged according to a conventional method to obtain a nano calcium carbonate product.

[0029] The nano calcium carbonate obtained from the embodiments of the present invention and the comparative embodiments was tested to obtain the results shown in Table 1. Photovoltaic adhesive was prepared according to the following formula, and the formula of the photovoltaic adhesive is shown in Table 2.

[0030] Table 1: Nano-calcium detection

[0031] Table 2: Preparation formula of photovoltaic adhesive

[0032] The plasticizer in the above formula is dioctyl phthalate (DOP), the crosslinking agent is diisopropyl peroxide (DCP): 2,5-dimethyl-2,5-di-tert-butyl peroxyhexane (bis-25) = 1:3, the coupling agent is γ-aminopropyltrimethoxysilane (KH-550), and the catalyst is dibutyltin dilaurate.

[0033] The preparation method of photovoltaic adhesive is as follows: Weigh each raw material according to the above mass fraction, put the weighed terminal hydroxyl polydimethylsiloxane, nano-calcium carbonate and plasticizer into a planetary agitator, dehydrate for 3 hours under the conditions of vacuum degree above -0.08MPa and temperature of 110-130°C to mix the materials evenly; cool to below 40°C, add cross-linking agent, coupling agent and catalyst to the system in sequence, continue to mix evenly under vacuum conditions for 30 minutes, then discharge and can, and the finished photovoltaic adhesive is obtained.

[0034] The test results of the photovoltaic adhesives obtained in various embodiments and comparative examples are shown in Table 3.

[0035] Table 3: Performance test results of photovoltaic adhesives made from various embodiments and comparative examples

[0036] From the above results and Figure 3 , Figure 4 It can be seen that the nano calcium carbonate modified by the embodiment of the present invention has differences in conventional tests compared with the comparative case, among which the oil absorption value is reduced, the BET is increased, and the moisture and whiteness are slightly improved. After the above nano calcium is made into photovoltaic glue, compared with the conventional nano calcium carbonate modification method, the mechanical properties and the effect of moisture and heat aging resistance are similar, and the effect of anti-ultraviolet performance is significantly enhanced.

Claims

1. A surface treatment method for anti-aging nano calcium carbonate of photovoltaic sealant, characterized in that: The following steps are involved: (1) Add nano calcium carbonate slurry into a reactor and heat it to 60-90°C; (2) adding the prepared surface treatment agent to the slurry of step (1) for surface treatment, and stirring to obtain modified nano calcium carbonate slurry; (3) Dehydrating, drying and crushing the obtained modified nano-calcium carbonate slurry to obtain a nano-calcium carbonate product.

2. The surface treatment method of anti-aging nano calcium carbonate for photovoltaic sealant according to claim 1, characterized in that: The specific surface area of ​​nano calcium carbonate is 15-35m2 / g, and the concentration of nano calcium carbonate slurry is 14%-17%.

3. The surface treatment method of anti-aging nano calcium carbonate for photovoltaic sealant according to claim 1, characterized in that: The surface treatment agent is a mixture of monostearate, 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine and sodium phosphite.

4. The surface treatment method of anti-aging nano calcium carbonate for photovoltaic sealant according to claim 3, characterized in that: The mass ratio of monostearate to 2,4,6-tris(4-carboxyphenyl)-1,3,5-triazine and sodium phosphite is 15-35:1:2-5.

5. The surface treatment method of anti-aging nano calcium carbonate for photovoltaic sealant according to claim 4, characterized in that: The added amount of the surface treatment agent is 0.1% to 0.5% of the mass of nano calcium carbonate.

6. The surface treatment method of anti-aging nano calcium carbonate for photovoltaic sealant according to claim 1, characterized in that: After adding the surface treatment agent, stirring is performed at 1200-1800 r / min to obtain modified nano calcium carbonate slurry.

7. The surface treatment method of anti-aging nano calcium carbonate for photovoltaic sealant according to claim 1, characterized in that: The drying temperature in step (3) is 105°C to 125°C.

8. A photovoltaic adhesive, characterized in that: The photovoltaic adhesive comprises the anti-aging nano calcium carbonate of the photovoltaic adhesive sealant prepared according to any one of claims 1-7.

Citation Information

Patent Citations

  • Preparation method of nano calcium carbonate for photovoltaic sealant

    CN116282115A

  • Method for preparing high-whiteness nanometer calcium carbonate special for silicone sealant by utilizing low-grade limestone by wet method

    CN101570342A

  • Surface treatment method for nano calcium carbonate special for photovoltaic adhesive

    CN105778568A

  • Special transmittance-increased and strength-increased masterbatch used for agricultural greenhouse ceiling film and preparation method thereof

    CN109280297A

  • Composite film, preparation method thereof and photovoltaic module

    CN118744576A

Cited By

  • Nano calcium carbonate with high humidity and heat performance for photovoltaic adhesive as well as preparation method and application of nano calcium carbonate

    CN121825280A

  • Highly adhesive sealant and method for preparing the same

    CN122790606A